Transparency and accountability in the Nepalese corporate sector: a critical assessment - Kharel, Saramsh; Magar, Sabina; Chaurasiya, Nitu; Maharjan, Sumi; Rijal, Chandra Prasad (Quest Journal of Management and Social Sciences, 2019)
Background: In the present changing context of Nepal, accountability and transparency may not only be treated as functionally interdependent, but also equally important in the process of maintaining effective governance in all contexts by imparting a system based on fairness, ethics, accountability, transparency and delivered quality. Therefore, it is essential for organizations to follow the pathways of sustainable governance in order to enhance their desired level system efficiency and effectiveness. Objectives: Primarily, the present work was accomplished to have a critical assessment of prevalence of corporate governance in the Nepalese corporate sector with focus on compliance of transparency and accountability. Methods: The present work was accomplished using a fully qualitative method of inquiry by performing a compliance review of transparency and accountability. Results: Universal evidence of existing literature confirms that accountability and transparency play vital role in transforming organizational trustworthiness. The practice of transparency provides access to convenient and reliable information required to enhance organizational decision-making, which ultimately results in improved level of performance. As a component ethical management, corporate governance, refers to the visionary proposition of organizational leadership for shared expectations of valued stakeholders. The world practices confirm that both transparency and accountability should go side by side to achieve quality and ethical organizational system practices, results and outcomes. Conclusions: Since Nepal is a new practitioner of modern concepts of corporate governance, its effective compliance is still infant. Thus, the Government of Nepal needs to devise and enact needful policy reforms. Implications: The present paper may serve instrumental as it attempts to analyze the existing evidences, discusses how approaches to learning of transparency and accountability might be improved, and recommends how the Nepalese corporate sector in the field of CG could be enhanced and empowered with a vision to sustainable corporate development and promotion in the country.